Manajemen Risiko sebagai pilar strategi dalam memperkuat Nasabah pada perbankan - Wahono, Dava Wahyu (Maliki Interdisciplinary Journal, 2026)
Thi This studyang aims to examine the role of risk management as a strategic approach in strengthening customer trust within the banking industry. As financial intermediaryang institutions, banks face various types of risks arising from both internal and external factors, including the increasing complexityang driven byang digital transformation. Therefore, the implementation of effective risk management is essential to maintain operational stabilityang and ensure business sustainability.This research employs a descriptive qualitative approach using secondaryang data obtained from literature studies, such as academic journals, books, and other relevant sources. Data were collected through documentation techniques and analyzed systematicallyang through interpretation and descriptive analysis. The findings indicate that risk management plays a significant role in maintaining financial stability, enhancing resilience against economic disruptions, and safeguarding customers’ funds and data. In addition, effective risk management contributes to improving customer trust and long-term loyalty. However, the banking sector also faces several challenges, including fraud risk, product complexity, rapid technological advancements, and limitations in human resources.To address these challenges, banks are required to implement comprehensive strategies, such as applying prudential principles, strengthening internal control systems, improving human resource competencies, ensuring transparency, and adopting good corporate governance practices. Thus, risk management not onlyang functions as a control mechanism but also serves as a strategic pillar in building customer trust and sustaining the stabilityang of the banking industry